The Influence of Leadership Styles on Organizational Commitment - Prem Ananthi, Bala Subramaniam (2011)
The objective of this study is to examine the influence of autocratic, transformational and servant leadership on organization commitment in XYZ Corporation. This study was conducted due to decreasing trend in organization commitment among the technological platform group of employees working in XYZ Corporation. A quantitative methodology was used and samples were taken from technological platform group of employees working in XYZ Corporation located in Penang. Data were collected from 101 employees by using simple random sampling. The data was analyzed using SPSS 12. The study indicates that there is a significant relationship between autocratic leadership and organization commitment. However, transformational leadership and servant leadership doesn't have a significant influence to organization commitment.